2010
DOI: 10.1007/s12664-010-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal hypertrophy and mast cells in histologically negative, clinically diagnosed acute appendicitis: a quantitative immunophenotypical analysis

Abstract: Neuronal hypertrophy and mast cells may play a role in the pathogenesis of appendicitis-like pain in patients with histologically normal appendices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…[14] Remaining two cases showed mucosal neuronal hyperplasia and one showed myenteric neuronal hyperplasia. These cases also had increased number of neutrophils similar to the study by Amber et al [15] Giant cell reaction was found in three cases. One case was associated with transmural inflammation though there was no other evidence of Crohn's disease.…”
Section: Shift To Left 1 Total 10 Rif: Right Iliac Fossasupporting
confidence: 87%
“…[14] Remaining two cases showed mucosal neuronal hyperplasia and one showed myenteric neuronal hyperplasia. These cases also had increased number of neutrophils similar to the study by Amber et al [15] Giant cell reaction was found in three cases. One case was associated with transmural inflammation though there was no other evidence of Crohn's disease.…”
Section: Shift To Left 1 Total 10 Rif: Right Iliac Fossasupporting
confidence: 87%
“…In about 20-25% of appendicectomies performed for clinically suspected acute appendicitis, definite morphological changes are lacking on histopathological examination. 1 Since appendectomy relieves pain, an unknown pathology is likely to exist. 2 The role of inflammatory reactions involving local endocrine cells and neuroproliferation in causing repeated attacks of pain has been described and several staining techniques including immunohistochemistry have been tried in detecting the pro-inflammatory mediators.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Although several studies have focused on the presence of neuronal hyperplasia/ hypertrophy (eg, increased numbers of ganglion cells) in the setting of clinical or histologically confirmed acute appendicitis, 1-3 none of these have demonstrated a predominance of swollen ganglion cells in small clusters or as single cells infiltrating the mucosa and superficial submucosa. As such, the current study is the first to highlight neuronal (ganglion cell) hyperplasia as a diagnostic pitfall in the differential diagnosis of goblet cell adenocarcinoma and signet-ring cell adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%